Стабилизатор ферментативной активности пероксидазы - Першина А. Г. Александра Геннадьевна; Сазонов А. Э. Алексей Эдуардович; Ефимова Л. В. Лина Викторовна; Лыткина О. А. Ольга Александровна; Итин В. И. Воля Исаевич; Магаева А. А. Анна Алексеевна; Терехова О. Г. Ольга Георгиевна; Найден Е. П. Евгений Петрович
Заглавие с титульного листа